2021
DOI: 10.1007/s11682-020-00442-z
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic and acquired pedophilia as two distinct disorders: an insight from neuroimaging

Abstract: Pedophilia is a disorder of public concern because of its association with child sexual offense and recidivism. Previous neuroimaging studies of potential brain abnormalities underlying pedophilic behavior, either in idiopathic or acquired (i.e., emerging following brain damages) pedophilia, led to inconsistent results. This study sought to explore the neural underpinnings of pedophilic behavior and to determine the extent to which brain alterations may be related to distinct psychopathological features in ped… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 76 publications
0
15
0
Order By: Relevance
“…Acquired pedophilic behavior (hereafter referred to as acquired pedophilia for brevity) refers to the insurgence of enacted pedophilic interests and/or urges as a symptom of brain insult of neurological origin [9,10]. The onset of acquired pedophilia has been described as a consequence of frontotemporal dementia [11,12], traumatic brain injury [13], surgical lesion [14], brain [15], or notochord [16] neoplasms, and multiple sclerosis [17,18] in individuals who have never overtly manifested pedophilic behavior before.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Acquired pedophilic behavior (hereafter referred to as acquired pedophilia for brevity) refers to the insurgence of enacted pedophilic interests and/or urges as a symptom of brain insult of neurological origin [9,10]. The onset of acquired pedophilia has been described as a consequence of frontotemporal dementia [11,12], traumatic brain injury [13], surgical lesion [14], brain [15], or notochord [16] neoplasms, and multiple sclerosis [17,18] in individuals who have never overtly manifested pedophilic behavior before.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the brain regions in which the synergic functioning is abnormal in the two forms of pedophilia are unknown. Regarding idiopathic pedophilia, some studies have attempted to shed light on structural or functional alterations [42,[47][48][49][50][51][52][53][54][55], but a recent meta-analysis concluded that the results do not spatially converge across different studies [10]; in other words, different studies have reported different results. Thus, to date, there are no consistent subtle brain alterations associated with developmental pedophilia.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations